Alzheimer’s Disease: The Review from Pathophysiology to Future Direction - Patel, Priya (Technoarete Transactions on Recent Research in Applied Microbiology and Biotechnology, 2023)
According to estimates from 2021, dementia, which affects 52 million people worldwide, is primarily caused by Alzheimer's disease (AD). Over 65 million individuals in India are 65 years of age or older and dementia is more common as people age. Moreover, the neurotransmitter acetylcholine deficiency and oxidative stress brought on by the aggravation of glutamatergic transmission are linked to AD. This number of new cases is over 30% higher than the incidence reported in the WHO. Even after over a century of research, the pathophysiology of Alzheimer's disease remains a mystery, and there is no treatment that causes natural recovery. Beta fragments and neurofibrillary tangles as previously established are crucial markers for Alzheimer's disease. These deposits arise as a result of native proteins folding incorrectly Alzheimer's disease is linked to inflammatory processes. Tacrine, donepezil, memantine and thiazolidines drugs are used in the treatment of this disease to control the symptoms. Keyword : Alzheimer's disease, Pathophysiology, Therapy.